513 THE INFLUENCE OF FRAILTY ON OUTCOMES FOR OLDER ADULTS ADMITTED TO HOSPITAL WITH BENIGN BILIARY AND PANCREATIC DISEASE. (14th June 2021) - Thomas, M; Baltatzis, M; Price, A; Pearce, L; Fox, J; Vilches-Moraga, A
Abstract: Introduction: The prevalence and complications of biliary disease increase with age. We describe the prevalence of frailty in older patients hospitalised with benign biliary and pancreatic disease and establish its association with mortality and duration of hospital stay. Methods: Prospective observational cohort study of patients aged 75 years and over admitted with a diagnosis of acute biliary disease to a surgical hospital unit between 17/09/2014 and 20/03/2017. Clinical Frailty Scale (CFS) score was recorded on admission. Results: We included 200 patients with a median age of 82 (75–99), 60% females, 89% lived in their homes, 154 (77%) were independent for personal and 99 (49.5%) for instrumental ADLs, 95% mobilised independently, 17.5% had memory impairment and 8% low mood. Acute cholecystitis was the most common diagnosis (43%) followed by acute cholangitis (36%) and acute pancreatitis (21%). 99 patients were non-frail (NF = CFS 1–4) and 101 were frail (F = CFS ≥5). 104 patients received medical treatment only. Surgery was more common in non-frail (F 2% vs. NF 11%), percutaneous drainage more frequently carried out in frail patients (15% vs. NF 5%) and endoscopic cholangiopancreatography (ERCP) was similar in both groups (F 32%vs. NF 31%). Frailty was associated with worse clinical outcomes in F vs. NF: functional deconditioning (34% vs. 11%), increased care level (19% vs 3%), length of stay (12 vs. 7 days), 90-day (8% vs. 3%) and 1 year-mortality (48% vs. 24%). Conclusion: Half of patients in our cohort of older adults hospitalised with acute biliary disease were frail. Higher scores of frailty are associated with increased mortality. Compared with non-frail patients, individuals living with frailty were less likely to undergo surgical treatment, spent longer in hospital and were less likely to remain alive at 12 months after hospital discharge.